Child participatory research methods: exploring grade 6 pupils' experiences of private tutoring in Kazakhstan. Issue 3 (4th May 2022) - Hajar, Anas; Sagintayeva, Aida; Izekenova, Zhanna
ABSTRACT: This paper used three participatory methods- children's drawings, photographs, and group interviews- along with a short questionnaire to explore Grade 6 pupils' experiences and perceptions of the private tutoring (PT) they had received in Nur-Sultan, Kazakhstan. The questionnaire data suggest that 316 out of 406 (79.87%) attended PT. The qualitative data from 30 pupils reveal that the participants' motives of having PT ranged from adult-imposed reasons (e.g. complying with parents' wishes by studying for an elite school place) to reasons associated with achieving their ideal selves by boosting their interest in learning and imagining themselves working/studying abroad or pursuing an international career. The participants acted as proactive agents by explaining not only the PT benefits but also its disadvantages, including the unethical practices of some schoolteachers, increasing tiredness and it being a potentially unfair advantage in a competitive context. This study suggested pedagogical implications and areas for ongoing research.